Clinical use of recombinant factor VIII Fc and recombinant factor IX Fc in patients with haemophilia A and B - Wang, C.; Young, G. (Haemophilia : the official journal of the World Federation of Hemophilia, 2018)
Introduction Although clinical trials have demonstrated extended half‐life (EHL) VIII and IX fusion proteins to be safe and efficacious in patients with haemophilia A and B, studies on real‐world clinical application have not been performed. Aim To retrospectively examine the real‐world experience of rFVIII Fc and rFIX Fc in patients. Methods A retrospective review of existing medical records of patients with haemophilia A or haemophilia B who had been prescribed rFVIII Fc or rFIX Fc was conducted from the Children's Hospital Los Angeles Haemostasis and Thrombosis Centre database. Results A total of 36 male subjects enroled in the study (17 patients with haemophilia A and 19 patients with haemophilia B; 0‐18 years of age, N = 27; >18 years of age, N = 9). Patients had a reduction of their ABR and AJBR following initiation of EHL factors. For patients with haemophilia A, the ABR and ABJR fell from 2.3 and 1.8 to 1.3 and 0.71, respectively. For patients with haemophilia B, the ABR and ABJR fell from 2.5 and 2.1 to 0.82 and 0.37, respectively. Five of 36 patients reverted from EHL back to standard half‐life (SHL) factor treatment. Overall, treatment with EHL factors reduced factor consumption by nearly half compared to treatment with SHL factors in patients with haemophilia B. Conclusion This study demonstrates the largely successful transition of 36 patients from SHL to EHL factor products.